An iterative algorithm for groundwater pumping energy cost minimization. Issue 6 (3rd June 2022) - Mallios, Zisis; Tsiarapas, Athanasios
Abstract : This article presents an algorithm for solving a very common water resources management problem. This involves finding the optimal solution to the problem of minimizing the cost of energy consumed during pumping and transporting water from a group of wells to a reservoir to satisfy the water needs of a residential area. This algorithm addresses the problem of minimizing the cost of the energy consumed by pumping groundwater through an iterative process. The results of the algorithm are verified by solving the same problem with the generalized reduced gradient algorithm, which is integrated into the Microsoft Excel Solver add-in. It is found that the algorithm accurately calculates the optimal solution of the problem, while the results of the solutions of similar mathematical programming problems with this algorithm can be used as guides for other more complicated problems.